Business App Development in Dynamics 365 for Non-Programmers - Briggs, Jimmy (Packt Publishing, 2020)
Build useful apps for mobile and the web using the PowerApp platform from Microsoft About This Video Create purposeful business apps that enable users to interact with information in meaningful ways without writing and maintaining any code or scripts Build apps intelligently to improve user productivity and the quality of customer and user data Efficiently roll out new apps as needed and quickly update and enhance your PowerApps as your business grows and evolves In Detail Hiring a developer to build a custom app, however small, is expensive. Microsoft PowerApps tackles this problem head-on and removes the programming aspect from app development. In this course, you will build visually stunning apps with intuitive user experiences - without writing a single line of code. Using a Lawn Care company's dataset you'll be building canvas and model-driven apps with a configuration-based approach to managing processes and data. This will revolutionize your ability to collect, analyze, and act on data. You will also learn how to set up SharePoint team sites in order to improve document storage and collaboration and reduce the space used by PowerApps. Finally, you will connect Power BI to your data so it can be combined with other systems in your company and provide rich user experiences to your leadership team. If you are a business user, manager, or consultant without any coding experience, this course will help you build and customize apps yourself! By the end of this course, you'll be able to build new apps or customize existing ones entirely on your own, without having to call in any programmers.